Characterization of insulation papers using FTIR-ATR spectroscopy - Planojević, Jelena; Lukić, Jelena; Vasović, Valentina; Mihajlović, Draginja; Janković, Jelena; Kovačević, Neda (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
Abstract. The need to increase the productivity and capacity of power transformers has conditioned the production of insulating papers of a higher thermal class. For this purpose, various techniques of solid insulation modification were applied, which enables the increase of thermal and chemical stability of the insulating paper during the operation of the transformer. The addition of additives, primarily dicyandiamide (DICY) and polyacrylamide (PAM), is one form of cellulose modification in the final stages of paper production. A significant difference between the papers is the nitrogen content in the paper, which is characterized by the addition of amine compounds (additives). The paper presents the application of infrared spectroscopy with totally attenuated reflection (FTIR-ATR) in the characterization of paper samples as the observation of the difference between regularly kraft and thermally upgraded paper reflected in the presence or absence of characteristic functional groups for additives. The strips identification at 2194-2154 cm-1 confirmed the presence of dicyandiamide additives (DICY) in the spectrum of the sample of thermally upgraded paper, which is different compared with the specter of regular kraft paper.
Keywords: power transformer, solid paper insulation, thermally upgraded paper, FT-ATR spectroscopy